Stakeholder pressure and environmental performance of manufacturing companies on the Indonesian stock exchange - Sari, Candra Widi; Sudana, I Putu; Ratnadi, Ni Made Dwi; Rasmini, Ni Ketut (Linguistics and Culture Review, 2022)
Environmental performance is the company's efforts to create a good environment. This study aims to empirically examine the effect of stakeholder pressure on environmental performance and the role of profitability in moderating the influence of Stakeholder Pressure on the environmental performance of manufacturing companies listed on the Indonesia Stock Exchange. The number of samples was 114, of which 38 manufacturing companies during the 2017-2020 observation year. This study uses a nonprobability sampling method with a purposive sampling technique. The data analysis technique uses moderated regression analysis. The study results show that Stakeholder Pressure, as proxied by environmental pressure, consumer pressure, employee pressure, and shareholder pressure, has a significant effect on the environmental performance of manufacturing companies listed on the Indonesia Stock Exchange. Profitability can moderate the influence of environmental pressure, consumer pressure, employee pressure, and shareholder pressure on the environmental performance of manufacturing companies listed on the Indonesia Stock Exchange.